Financial frictions, crises, return predictability, and managerial moral hazard - Doshchyn, A (2021)
Chapter 1. While financial crises tend to be preceded by credit booms, most credit booms do not end up in crises. Crises typically occur when there is also a persistent slowdown in productivity growth. I develop a model in which risk of crisis emerges endogenously during boom because of increased fragility of the banking sector. Banks raise financing from households to invest in long-term projects, but their ability to do so is limited by moral hazard. Demandable deposits create discipline by exposing misbehaving banks to runs, and thus help them increase external financing. Normally, banks finance themselves with a mix of equity and deposits that maximizes discipline, but ensures that they always remain solvent. When growth prospects become sufficiently strong, however, worsening moral hazard induces banks to rely exclusively on deposit financing, which enables a boom in credit, asset prices, and investment. If the anticipated growth fails to materialise, though, the excessive deposit financing leads to a systemic banking crisis. I also study policy implications of the model.